Effects of a golfers` low back pain exercise prevention program on physical function and golf performance in adolescent golfers: a double-blind, randomized, sham-controlled trial - Hamada, Y.; Akasaka, K.; Okubo, Y.; Hattori, H.; Mizoguchi, Y.; Kikuchi, Y.; Nakagawa, H.; Hall, T. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Purpose Injury prevention programs for adolescent athletes include pre-game exercise programs designed to improve individuals physical function. This study aimed to determine the impact of Golfers` Low back pain Exercise prevention Program (GLEP) on physical function and golf performance.